Radiation-related properties of additive-manufactured materials in relativistic electron beam studies; Radiation from Relativistic Electrons in Periodic Structures, RREPS-25 - Bulavskaya A. A. Angelina Aleksandrovna; Polomoshnova D. A. Darjya Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2025, 2025)
Title screen